Sarcopenia na doença de Parkinson: avaliação clínica, risco de quedas e protocolo de reabilitação - Lima, Danielle Pessoa (2021)
Parkinson's Disease (PD) is the second most prevalent neurodegenerative disease in Brazil, present in about 1% of the elderly over 65 years of age and between 4 to 5% in those over 85 years of age. It is a chronic, progressive, and disabling disorder, with motor and non-motor symptoms, compromising quality of life. Genetic factors, oxidative stress, environmental toxins, and mitochondrial abnormalities are involved in its pathophysiology. The parkinsonian syndrome consists of four cardinal signs: resting tremor, muscle rigidity, akinesia or bradykinesia, and postural instability. Bradykinesia is a required feature for the diagnosis accompanied by one more sign. Sarcopenia is a complex and multifactorial condition characterized by reduced quantity and/or quality of skeletal muscle tissue. The pathophysiology of sarcopenia has elements in common with PD and involves mitochondrial dysfunction, increased oxidative stress, inflammation, imbalance in protein metabolism (greater degradation than synthesis). In sarcopenia, other determining factors are decrease in hormones and growth factors and proteins that maintain adequate cell functions, decline in essential nutrient intake, decline in physical activity. Most of these contributors are not unique to the muscular system, they can also apply to the nervous system. It is common in PD, and severe sarcopenia is diagnosed in 1 out of 5 parkinsonian patients. Power training (PT) is a more effective intervention than strength training in gait performance and risk of falls. Elastic bands and tubes are simple tools for PT, allowing you to work all major muscle groups. This thesis consisted of evaluating the prevalence of sarcopenia in PD and its repercussions, developing a protocol of PT and, subsequently, investigating its viability in this population. A cross-sectional study was carried out at the Movement Disorders Outpatient Clinic in Fortaleza, Brazil, where 218 patients with PD were evaluated, of which 121 (55.5%) were classified as possible sarcopenic by SARC-F and 103 (47.4%) as likely probable sarcopenics. Sarcopenia was associated with worse quality of life and falls. A “PARK-BAND” intervention protocol was developed, a randomized, single-blind, unicentric, two-arm parallel study for 12 weeks, which will include 50 participants with PD, with the purpose of evaluating the potential benefits of PT, using elastic devices. Participants will be randomized in a 1:1 ratio to the PT group and the health education group (HEG). The primary outcomes will be the bradykinesia score from the Unified Parkinson's Disease Rating Scale motor exam and the functional physical performance, assessed by the Short Physical Performance Battery. The HEG will receive a booklet with 12 chapters with strategies to live well with the disease (1x/week, 50-60 minutes). The PT is based on fast movements with low resistance loads, the movement being as fast as possible in the concentric phase and slower in the eccentric phase (2x/week, 50-60 minutes). It is required to complete at least 85% of the planned sessions. Feasibility study of this protocol was carried out. Thirty-four patients were screened at telephone recruitment to include 8 eligible, of which 5 (62.5%) were women with a median age of 66 (45-77) years. The attendance rate to the HEG was 83.3% and to the PT 96.82%, the adherence rate to the HEG was 80% and to the PT 95.23%, the retention rate was 75% in both groups, no adverse events. Sarcopenia has many pathophysiological changes in common with a PD. Sarcopenia will lead to functional loss and falls. Optimizing muscle function is essential to improve quality of life, risk of falling, and motor symptoms of bradykinesia. Based on these results, we intend to validate the criteria for confirmed sarcopenia in PD and carry out the PARK-BAND study. Based on these results, we intend to validate the criteria for confirmed sarcopenia in PD, validate the booklet and carry out the Park-Band study.